Exploring Islamic Spiritual Well-Being: Conceptualization and Validation of a Measurement Scale - Bagis, Fatmah; Adawiyah, Wiwiek Rabiatul; Purnomo, Ratno; Sudjadi, Achmad (Islamic Guidance and Counseling Journal, 2024)
Islamic Spiritual Well-Being (ISWB) constitutes a novel theoretical framework amalgamating management perspectives with Quranic and Sunnah principles, yet its exploration remains limited. This research endeavors to fill this gap by synthesizing insights from management perspectives and Islamic literature to develop a precise conceptualization and validation of a measurement ISWB. Through practitioner and expert interviews, ISWB is delineated as a state marked by positive emotions emanating from adherence to Islamic principles, fostering Allah’s satisfaction, assistance, and forgiveness, particularly in organizational contexts. Employing a rigorous methodological approach that integrates qualitative and quantitative methodologies, including conceptual and indicator development, content validity, and statistical analyses, the study seeks to portray the construct of ISWB within organizational settings comprehensively. By furnishing a validated measurement scale, this study contributes a robust framework for assessing and comprehending religious behaviors and experiences in Islamic contexts, thereby enhancing understanding of the intricate interplay between spirituality, ethics, and individual behavior, with implications for Islamic-based organizations and future research endeavors.